DUKUNGAN ORANG TUA DALAM PENGEMBANGAN LITERASI ANAK DI RUMAH PADA MASA NEW NORMAL - Prita Ridha Insani; Elise Muryanti (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This research is motivated by the importance of developing literacy at an early age. In this New Normal era, parents play an important role in educating children from home, including in the development of children's literacy. The purpose of this study is to find out parental support is in developing children's literacy from home during the New Normal period in Raudhatul Iman Kindergarten, Kampung Jua Village, Padang City. This research was conducted by using the quantitative descriptive method. Sampling used a total sampling technique, namely 31 parents at Raudhatul Iman Kindergarten in the 2020/2021 academic year. The instrument used is a questionnaire distributed online. Meanwhile, for data analysis using percentage classification. The findings of this study reveal that parental support in (1) in the development of children's literacy in the new normal period is in Good criteria, (2) children's literacy development at home during the new normal from the aspect of vocabulary skills is in Good Criteria, and (3) the development of children's literacy at home during the new normal period from the aspect of Skill Motivation is in the Good Criteria.